Pioglitazone repurposing via in-situ gelling system: An effective topical strategy for wound management - Abdelkader, Dalia H.; Elshaer, Samar M.; Elkordy, Eman A.; Sarhan, Naglaa I.; Essa, Ebtessam A. (Journal of drug delivery science and technology, 2025)
This study investigated pioglitazone hydrochloride (PGZ), an antidiabetic drug, as a wound healing promoter employing the in-situ gel approach. Poloxamer 407 was selected due to its thermo-reversible sol-gel transition properties, in the presence or absence of chitosan. PGZ solubility was enhanced by the solid dispersion (SD) technique, using Hydroxypropyl methylcellulose (HPMC) as a matrix former. SDs increased PGZ solubility up to 3.3-fold due to increased drug wettability and modulated drug crystallinity as reflected from thermal analysis. In-situ gel systems, loaded with optimized SD, were prepared at 14–20%w/v of Poloxamer-407. Chitosan (0.5%w/v) was added to some formulations. In-vitro characterization was performed regarding viscosity, pH, gelation temperature, gelation time, and in-vitro release profiles. All formulations displayed a prolonged release pattern, with hybrid polymeric in-situ gel formula F5 showing suitable gelation time (18.8 ± 1.0 s), gelation temperature (33.9 ± 0.1 °C), viscosity value of 1332 ± 1.0 cP (at 34 °C) and a pH of 5.6 ± 0.1. F5 also showed the highest cumulative drug release (47.5 % ± 0.3) over 8 h with acceptable mucoadhesive properties with a tensile strength value of 11.9 ± 1.5 N/mm2. This formulation was stable after one month of storage at 4 °C, room temperature, and accelerated conditions. The wound healing ability of F5 was investigated using Wistar albino rats. The wound contraction was highest in the in-situ gel, compared to PGZ suspension. Histopathological examination (H&E, Masson trichrome, and α SMA) reflected the superiority of the optimized system in restoring the normal architecture of the skin. [Display omitted]